x(x+3)-3=3x+1

Simple and best practice solution for x(x+3)-3=3x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+3)-3=3x+1 equation:


Simplifying
x(x + 3) + -3 = 3x + 1

Reorder the terms:
x(3 + x) + -3 = 3x + 1
(3 * x + x * x) + -3 = 3x + 1
(3x + x2) + -3 = 3x + 1

Reorder the terms:
-3 + 3x + x2 = 3x + 1

Reorder the terms:
-3 + 3x + x2 = 1 + 3x

Add '-3x' to each side of the equation.
-3 + 3x + -3x + x2 = 1 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + 0 + x2 = 1 + 3x + -3x
-3 + x2 = 1 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + x2 = 1 + 0
-3 + x2 = 1

Solving
-3 + x2 = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + x2 = 1 + 3

Combine like terms: -3 + 3 = 0
0 + x2 = 1 + 3
x2 = 1 + 3

Combine like terms: 1 + 3 = 4
x2 = 4

Simplifying
x2 = 4

Take the square root of each side:
x = {-2, 2}

See similar equations:

| 14-x=37 | | 7y-3=17 | | x^2+kx+8=k | | 5(m+4)-7= | | 5*x^2-x^2=36 | | 2(x^2-192)=0 | | .66d+1=16-d | | 2(x-3)+5=4x+7 | | -(a-4)=6 | | 10(a+1)-14a=9+(4a-1) | | 0=2x^3-6x^2+8x-3 | | -2(4x-9)=-8x+18 | | 7+5y=39+y | | 119+40+4x=180 | | 400-40w=80 | | 125.00+5.75=228.50 | | 9xh=-63 | | 6x-43=65+x | | 4x-15=1x-13 | | 3/2x+6+1/2x=15+x | | 3x+2y-5x+7y= | | -742+524= | | (x+y)*(x-y)=17 | | 4x+5+7x-7=180 | | y=6mx-3b | | 4.9=-9+x | | -.833=x-.333 | | 19=3(-4b-3)+5b | | 8+3x/5=11 | | 2=2-3r-5r | | -1-(1-c)=2c-11 | | w+12=19 |

Equations solver categories